Risk factors for neo‐osteogenesis in cystic fibrosis and non‒cystic fibrosis chronic rhinosinusitis. Issue 4 (19th December 2019) - Karempelis, Peter; Karp, Emily; Rubin, Nathan; Hunter, Ryan; Dunitz, Jordan; Boyer, Holly
Abstract : Background: The purpose of this retrospective review was to determine how patient‐related factors and culture data affect neo‐osteogenesis in patients with chronic rhinosinusitis (CRS) and patients with cystic fibrosis (CF) with CRS. Methods: Information from a database associated with a large tertiary medical center was used to assess adult patients with CF CRS and non‐CF CRS (total, n = 102; CF CRS, n = 31; non‐CF CRS, n = 71). Radiologic evidence of neo‐osteogenesis was measured using the Global Osteitis Scoring Scale (GOSS), and mucosal disease was assessed using the Lund‐Mackay score (LMS) by 2 independent reviewers who were blinded to the patient's disease state. Bacterial cultures were obtained endoscopically. Multiple logistic regression models were used to evaluate the effect of age, sex, number of previous surgeries, CF, and culture species on the odds of neo‐osteogenesis. Results: Fifty‐one of the 102 patients (50%) met radiologic criteria for neo‐osteogenesis. Sixty‐nine patients (67.6%) with CF CRS and non‐CF CRS had culture data. In the multiple logistic regression model, male gender was significantly associated with neo‐osteogenesis (odds ratio [OR], 5.2; 95% confidence interval [CI], 1.68‐17.86; p = 0.006). Pseudomonas aeruginosa was not associated with neo‐osteogenesis (OR, 3.12; 95% CI, 0.84‐12.80; p = 0.097). Age, number of surgeries, CF, Staphylococcus aureus, and coagulase‐negative Staphylococcus were not statistically significant. Conclusion: To our knowledge, this is the first study to assess risk factors associated with neo‐osteogenesis and patients with CF CRS. Interestingly, male gender was the only significant predictor of neo‐osteogenesis.